VIRTUAL REALITY FOR MEDICAL TRAINING: NOTES ON OPPORTUNITIES AND CHALLENGES - Miguel Melo (PsychTech & Health Journal)
Training with virtual reality (VR) technologies is an expanding application field. Healthcare can largely benefit from it as VR offers many advantages over conventional training methodologies, especially when the goal is to train specialized technicians (Narciso et al., 2019).